Clinically meaningful improvements after gene therapy for aromatic L-amino acid decarboxylase deficiency (AADCd) in the Peabody Developmental Motor Scale, Second Edition (PDMS-2) and correlation with Bayley-III scores and motor milestones - Wuh-Liang Hwu; Hui-Min Lee; John Devin Peipert; Rongrong Zhang; Christian Werner; J. Rafael Sierra; Thomas O’Connell; Jonathan J. Woolley; Marjorie Crowell; Antonia Wang; Ioannis Tomazos (Orphanet Journal of Rare Diseases)
Abstract Background Aromatic L-amino acid decarboxylase deficiency (AADCd) is a rare genetic disorder characterized by movement disorders, motor and autonomic dysfunction, and developmental delays. The gene therapy eladocagene exuparvovec has become available in some regions; pooled clinical trial results demonstrate continuous long-term improvement in motor development and cognitive function. We sought to characterize clinically meaningful change in motor function, as measured by Total Peabody Developmental Motor Scales-Second Edition (PDMS-2) score, and assess correlations with cognition and language domains of the Bayley-III and motor milestone (MM) achievement. Methods Data from N = 30 patients from three single-arm clinical studies of eladocagene exuparvovec were analyzed. Anchor-based estimation of the meaningful score difference (MSD) of Total PDMS-2 score was conducted using mean-difference and receiver operating characteristic curve (ROC) approaches. MM achievement served as the anchor defining meaningful change. Results An MSD of 40 points for Total PDMS-2 score was selected for analysis as it yielded specificity > 0.95 using the ROC approach, and generally aligned with the mean-difference approach. Cumulative incidence analysis reflected that 50% of patients treated with eladocagene exuparvovec may achieve the MSD of 40-point change in Total PDMS-2 score at 6 months, and 86% at 18 months. Correlations between measures were of large magnitude and improved over time (Month 6: r = 0.599 [p = 0.0032]; Month 18: r = 0.796 [p = 0.0002]; Month 60: r = 0.861 [p = 0.0007]). Conclusions The MSD of 40 points for Total PDMS-2 score enables the interpretation of changes observed in patients with AADCd, and suggests that treatment with eladocagene exuparvovec leads to significant improvements in motor and cognitive function.